Sialic acid methylation refines capillary electrophoresis laser‐induced fluorescence analyses of immunoglobulin G N‐glycans of ovarian cancer patients. Issue 7 (5th March 2014) - Schwedler, Christian; Kaup, Matthias; Petzold, Dominique; Hoppe, Berthold; Braicu, Elena Iona; Sehouli, Jalid; Ehlers, Marc; Berger, Markus; Tauber, Rudolf; Blanchard, Véronique; Phillips, Terry M.
<x xml:space="preserve">Abstract</x> Alterations in IgG N‐glycosylation coincide with the development of a number of diseases including cancer and could potentially be used as diagnostic markers. CE‐LIF of 8‐aminopyrene‐1, 3, 6‐trisulfonic acid labeled N‐glycans is a well‐established rapid method to characterize IgG N‐glycans that needs only low amounts of starting material. However, sialylated N‐glycans have short migration times due to their negative charge. As a result, some of them are not well resolved and co‐migrate with neutral glycans. In this work, we neutralized the negative charge of sialic acids by methylation and optimized the protocol using the commercially available disialylated biantennary oligosaccharide (A2G2S2). IgG N‐glycans isolated from healthy human serum were then analyzed using this method. We could demonstrate that co‐migration of A2, FA2G2S1, and FA2B[3]G1S1 was prevented, which allowed an accurate quantification of these N‐glycans. Finally, we investigated the IgG N‐glycan profiles of patients suffering from ovarian cancer using the conventional and methylation methods. With both methods, we observed an increase of agalactosylated structures that was accompanied by a decrease in digalactosylated structures. Finally, using the methylation protocol, we could further demonstrate an increase of A2, which was technically impossible with the conventional method.